Is Severe Neck Pain a Contraindication to Performing Laminoplasty in Patients With Cervical Spondylotic Myelopathy?. Issue 3 (13th April 2023) - Pinter, Zachariah W.; Mikula, Anthony L.; Reed, Ryder; Lakomkin, Nikita; Townsley, Sarah E.; Wright, Breydan; Kazarian, Erick; Michalopoulos, Giorgos D.; Currier, Bradford; Freedman, Brett A.; Bydon, Mohamad; Elder, Benjamin D.; et al.
Abstract : Study Design: Retrospective review. Objective: The purpose of this study was to investigate the surgical outcomes in a cohort of patients with severe preoperative axial neck pain undergoing laminoplasty for cervical spondylotic myelopathy (CSM). Summary of Background Data: No study has investigated whether patients with severe axial symptoms may achieve satisfactory neck pain and disability outcomes after laminoplasty. Methods: We performed a retrospective review of 91 patients undergoing C4-6 laminoplasty for CSM at a single academic institution between 2010 and 2021. Patient-reported outcome measures (PROMs), including Neck Disability Index (NDI), visual analog scale (VAS) Neck, and VAS Arm, were recorded preoperatively and at 6 months and 1 year postoperatively. Patients were stratified as having mild pain if VAS neck was 0–3, moderate pain if 4–6, and severe pain if 7–10. PROMs were then compared between subgroups at all the perioperative time points. Results: Both the moderate and severe neck pain subgroups demonstrated a substantial improvement in VAS neck from preoperative to 6 months postoperatively (−3.1±2.2 vs. −5.6±2.8, respectively; P <0.001), and these improvements were maintained at 1 year postoperatively. There was no difference in VAS neck between subgroups at either the 6-month or 1-year postoperative time points. Despite the substantially higher mean NDI in the moderate and severe neck pain subgroups preoperatively, there was no difference in NDI at 6 months or 1 year postoperatively ( P =0.99). There were no differences between subgroups in the degree of cord compression, severity of multifidus sarcopenia, sagittal alignment, or complications. Conclusions: Patients with moderate and severe preoperative neck pain undergoing laminoplasty achieved equivalent PROMs at 6 months and 1 year as patients with mild preoperative neck pain. The results of this study highlight the multifactorial nature of neck pain in these patients and indicate that severe axial symptoms are not an absolute contraindication to performing laminoplasty in well-aligned patients with CSM.